Diego Petersen Farah, Casquillos negros (México, Tusquets, 2017, 241 pp. ISBN 978-607-07-3905-7) (Altre Modernità, 2018)
Diego Petersen Farah, Casquillos negros (México, Tusquets, 2017, 241 pp. ISBN 978-607-07-3905-7)por Anamaría González Luna C.